Reductive carboxylation and 2-hydroxyglutarate formation by wild-type IDH2 in breast carcinoma cells - Smolková, Katarína; Dvořák, Aleš; Zelenka, Jaroslav; Vítek, Libor; Ježek, Petr (The international journal of biochemistry & cell biology, 2015)
Mitochondrial NADPH-dependent isocitrate dehydrogenase, IDH2, and cytosolic IDH1, catalyze reductive carboxylation of 2-oxoglutarate. Both idh2 and idh1 monoallelic mutations are harbored in grade 2/3 gliomas, secondary glioblastomas and acute myeloid leukemia. Mutant IDH1/IDH2 enzymes were reported to form an oncometabolite r-2-hydroxyglutarate (2HG), further strengthening malignancy. We quantified CO2-dependent reductive carboxylation glutaminolysis (RCG) and CO2-independent 2HG production in HTB-126 and MDA-MB-231 breast carcinoma cells by measuring (13)C incorporation from 1-(13)C-glutamine into citrate, malate, and 2HG. For HTB-126 cells, (13)C-citrate, (13)C-malate, and (13)C-2-hydroxyglutarate were enriched by 2-, 5-, and 15-fold at 5mM glucose (2-, 2.5-, and 13-fold at 25 mM glucose), respectively, after 6 h. Such enrichment decreased by 6% with IDH1 silencing, but by 30-50% upon IDH2 silencing while cell respiration and ATP levels rose up to 150%. Unlike 2HG production RCG declined at decreasing CO2. At hypoxia (5% O2), IDH2-related and unrelated (13)C-accumulation into citrate and malate increased 1.5-2.5-fold with unchanged IDH2 expression; whereas hypoxic 2HG formation did not. (13)C-2HG originated by ∼50% from other than IDH2 or IDH1 reactions, substantiating remaining activity in IDH1&2-silenced cells. Relatively high basal (12)C-2HG levels existed (5-fold higher vs. non-tumor HTB-125 cells) and (13)C-2HG was formed despite the absence of any idh2 and idh1 mutations in HTB-126 cells. Since RCG is enhanced at hypoxia (frequent in solid tumors) and 2HG can be formed without idh1/2 mutations, we suggest 2HG as an analytic marker (in serum, urine, or biopsies) predicting malignancy of breast cancer in all patients.
Keywords: NADPH-dependent isocitrate dehydrogenase IDH2; hypoxie buňky; Oxygen; Breast carcinoma HTB-126 cells; Cell Line, Tumor; Partial Pressure; Glutarates; Hypoxia; nádory prsu; glutaráty; isocitrátdehydrogenasa; Breast adenocarcinoma MDA-MB-231 cells; Isocitrate Dehydrogenase; lidé; kyslík; parciální tlak; ženské pohlaví; Cell Hypoxia; Breast Neoplasms; Humans; Oncometabolite r-2-hydroxyglutarate; nádorové buněčné linie; Female; Biomarkers, Tumor; nádorové biomarkery; Reductive carboxylation